The determinants of investment account holders' disclosure in Islamic banks: International evidence - Raoudha Saidani; Neila Boulila Taktak; Khaled Hussainey (Journal of Risk and Financial Management, 2021)
In this paper, we offer a novel contribution to Islamic accounting literature by examining the determinants of Investment Account Holder (IAH) disclosure in Islamic banks' annual reports. Using data from Islamic banks around the world, our regression analysis shows that the level of IAH funds, the return on IAH funds, adoption of AAOIFI standards, liquidity level, bank size and ownership have a positive significant relationship with IAHs' disclosure level. Our findings can be useful for IAHs, regulatory bodies and information users in general as they help them to understand IAH practices in Islamic banks and the main incentives of managers to disclose IAHs' information. The present study offers an original contribution to the Islamic accounting literature as it is the first one-to the best of our knowledge-that investigates the relationship between the specificities of Islamic banks and the extent of IAH disclosure.
Keywords: 330; Investment Account Holders; AAOIFI standards; disclosure; Islamic banks